Prevalence of Vitamin D Deficiency among Patients Attending Tertiary Level Hospitals in Bangladesh: Hospital-Based Cross-Sectional Study (Medicine Today, 2024)
Introduction: Vitamin D (Vit D) is essential for calcium and phosphate homeostasis, critical for bone growth and remodeling. Its deficiency leads to conditions like osteomalacia and rickets, with adverse effects on osteoporosis, growth, and skeletal health. This study aimed to assess Vitamin D Deficiency prevalence among patients in Bangladeshi tertiary-level hospitals. Materials and Methods: A prospective cross-sectional study was conducted from January to December 2019 at Cumilla Medical College Hospital and Central Medical College Hospital. We enrolled 1250 patients meeting inclusion criteria and collected data via a pre-designed questionnaire. Results: Most participants (31.8%) were aged 31-40, with a mean age of 37.31±13.37. Male patients constituted 53.3%, and 46.7% were female. Rural residents accounted for 52.6%, while 25.8% lived in urban areas, and the rest abroad, mainly the Middle East. The majority (88.5%) belonged to middle-class families, and only 1.5% reported sufficient sun exposure. Strikingly, 54.2% were Vitamin D deficient, 40% had insufficient levels, and only 6.4% had adequate Vit D. Conclusion: This study highlights a significant prevalence of Vitamin D deficiency among patients in Bangladeshi tertiary hospitals. The data underscore the urgent need for healthcare authorities to address this public health concern. Policymakers and healthcare providers should be aware of the potential long-term health consequences of Vitamin D deficiency, emphasizing the importance of strategies to promote adequate Vit D levels in the population.Medicine Today 2023 Vol.36 (1): 17-22